2022
DOI: 10.1093/ageing/afac192
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and impact of frailty in patients with atrial fibrillation in Europe

Abstract: Background Frailty is a medical syndrome characterised by reduced physiological reserve and increased vulnerability to stressors. Data regarding the relationship between frailty and atrial fibrillation (AF) are still inconsistent. Objectives We aim to perform a comprehensive evaluation of frailty in a large European cohort of AF patients. Methods A 40-item fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…We found that apixaban was associated with not only a reduction in clinical events but also a smaller risk of home time lost greater than 14 days during 365 days, a threshold that correlated with worsening mobility impairment, depression, and difficulty in self-care . The association favoring apixaban was stronger among beneficiaries with frailty, reflecting the higher background risks and disease burden in patients with frailty …”
Section: Discussionmentioning
confidence: 75%
“…We found that apixaban was associated with not only a reduction in clinical events but also a smaller risk of home time lost greater than 14 days during 365 days, a threshold that correlated with worsening mobility impairment, depression, and difficulty in self-care . The association favoring apixaban was stronger among beneficiaries with frailty, reflecting the higher background risks and disease burden in patients with frailty …”
Section: Discussionmentioning
confidence: 75%
“… 26 Frail older patients are less likely to receive anticoagulation with warfarin in both inpatient and outpatient settings, are significantly more likely to experience embolic stroke and have higher mortality rates; but do not have a significantly increased risk of major hemorrhage. 27 In a recent large cohort study of AF patients, the clinical benefit of OAC was maintained in AF patients with varying levels of frailty, including those with moderate to high levels of frailty but not in end-stage frailty. 28 It is therefore important to recognize that frailty alone should not preclude the use of OACs in elderly patients with AF.…”
Section: Discussionmentioning
confidence: 98%
“…Frailty is a clinical syndrome that is frequently found in cardiology patients, characterized by reduced physiological reserve and increased vulnerability to stressors [ 38 , 39 ]. Several studies reported that frail patients are associated with an increased risk of adverse outcomes, thus requiring structured and holistic clinical management [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%